Cholesterol-Lowering Probiotics as Potential Biotherapeutics for Metabolic Diseases. (3rd May 2012) - Kumar, Manoj; Nagpal, Ravinder; Kumar, Rajesh; Hemalatha, R.; Verma, Vinod; Kumar, Ashok; Chakraborty, Chaitali; Singh, Birbal; Marotta, Francesco; Jain, Shalini; Yadav, Hariom
Abstract : Cardiovascular diseases are one of the major causes of deaths in adults in the western world. Elevated levels of certain blood lipids have been reported to be the principal cause of cardiovascular disease and other disabilities in developed countries. Several animal and clinical trials have shown a positive association between cholesterol levels and the risks of coronary heart disease. Current dietary strategies for the prevention of cardiovascular disease advocate adherence to low-fat/low-saturated-fat diets. Although there is no doubt that, in experimental conditions, low-fat diets offer an effective means of reducing blood cholesterol concentrations on a population basis, these appear to be less effective, largely due to poor compliance, attributed to low palatability and acceptability of these diets to the consumers. Due to the low consumer compliance, attempts have been made to identify other dietary components that can reduce blood cholesterol levels. Supplementation of diet with fermented dairy products or lactic acid bacteria containing dairy products has shown the potential to reduce serum cholesterol levels. Various approaches have been used to alleviate this issue, including the use of probiotics, especially Bifidobacterium spp. and Lactobacillus spp.. Probiotics, the living microorganisms that confer health benefits on the host when administered in adequate amounts, have received much attention on their proclaimed health benefits which include improvement in lactose intolerance, increase in natural resistance to infectious disease in gastrointestinal tract, suppression of cancer, antidiabetic, reduction in serum cholesterol level, and improved digestion. In addition, there are numerous reports on cholesterol removal ability of probiotics and their hypocholesterolemic effects. Several possible mechanisms for cholesterol removal by probiotics are assimilation of cholesterol by growing cells, binding of cholesterol to cellular surface, incorporation of cholesterol into the cellular membrane, deconjugation of bile via bile salt hydrolase, coprecipitation of cholesterol with deconjugated bile, binding action of bile by fibre, and production of short-chain fatty acids by oligosaccharides. The present paper reviews the mechanisms of action of anti-cholesterolemic potential of probiotic microorganisms and probiotic food products, with the aim of lowering the risks of cardiovascular and coronary heart diseases.